Coenzyme Q biosynthesis inhibition induces HIF‐1α stabilization and metabolic switch toward glycolysis. (20th September 2020) - Liparulo, Irene; Bergamini, Christian; Bortolus, Marco; Calonghi, Natalia; Gasparre, Giuseppe; Kurelac, Ivana; Masin, Luca; Rizzardi, Nicola; Rugolo, Michela; Wang, Wenping; Aleo, Serena J.; Kiwan, Alisar; et al.
Abstract : Coenzyme Q10 (CoQ, ubiquinone) is a redox‐active lipid endogenously synthesized by the cells. The final stage of CoQ biosynthesis is performed at the mitochondrial level by the 'complex Q', where coq2 is responsible for the prenylation of the benzoquinone ring of the molecule. We report that the competitive coq2 inhibitor 4‐nitrobenzoate (4‐NB) decreased the cellular CoQ content and caused severe impairment of mitochondrial function in the T67 human glioma cell line. In parallel with the reduction in CoQ biosynthesis, the cholesterol level increased, leading to significant perturbation of the plasma membrane physicochemical properties. We show that 4‐NB treatment did not significantly affect the cell viability, because of an adaptive metabolic rewiring toward glycolysis. Hypoxia‐inducible factor 1α (HIF‐1α) stabilization was detected in 4‐NB‐treated cells, possibly due to the contribution of both reduction in intracellular oxygen tension and ROS overproduction. Exogenous CoQ supplementation partially recovered cholesterol content, HIF‐1α degradation, and ROS production, whereas only weakly improved the bioenergetic impairment induced by the CoQ depletion. Our data provide new insights on the effect of CoQ depletion and contribute to shed light on the pathogenic mechanisms of ubiquinone deficiency syndrome. Abstract : The inhibition of coq2 by 4‐nitrobenzoate decreases the CoQ content, promoting the biosynthesis of cholesterol. The increased cholesterol content reduces the plasma membrane fluidity, lowering intracellular oxygen tension. The OxPhos activity and the antioxidant defences are decreased. These conditions favor the stabilization of hypoxia‐inducible factor 1α, which mediates the adaptive metabolic response stimulating the glycolytic pathway, with enhanced glucose entry and induction of the PMOR system to lessening the intracellular reducing power.